PTPN2 Downregulation Is Associated with Albuminuria and Vitamin D Receptor Deficiency in Type 2 Diabetes Mellitus - Li Zheng; Wei Zhang; Aimei Li; Yan Liu; Bin Yi; Farid Nakhoul; Hao Zhang (Journal of Diabetes Research)
Objective. Inflammation plays a major role in albuminuria in type 2 diabetes mellitus (T2DM). Our previous studies have shown that the expression of vitamin D receptor (VDR) is downregulated in T2DM which is closely associated with the severity of albuminuria. In this study, we investigated the expression of anti-inflammatory cytokine protein tyrosine phosphatase nonreceptor type 2 (PTPN2) in T2DM and explored its relationship to albuminuria and VDR. Methods. 101 T2DM patients were divided into three groups based on urinary albumin-to-creatinine ratio (uACR): normal albuminuria (uACR < 30 mg/g, n=29), microalbuminuria (30 mg/g ≤ uACR < 300 mg/g, n=34), and macroalbuminuria (uACR ≥ 300 mg/g, n=38). Thirty healthy individuals were included as controls. Serum was analyzed for PTPN2 and IL-6 expression, and peripheral blood mononuclear cells (PBMCs) were analyzed for PTPN2 and VDR expression. THP-1 cells were incubated with high glucose and further treated with or without paricalcitol, a vitamin D analog. The levels of PTPN2, VDR, IL-6, TNFα, and MCP-1 were analyzed. In addition, anti-inflammatory activities of PTPN2 were further explored in THP-1 cells stimulated with high glucose after PTPN2 silencing or overexpression. Results. PTPN2 expression was downregulated in T2DM with the lowest level observed in macroalbuminuria patients. PTPN2 level positively correlated with VDR but negatively correlated with uACR and IL-6. When stimulated with high glucose, there was an increase in inflammatory factors and a decrease in PTPN2 expression. Treatment with paricalcitol reversed these effects. However, paricalcitol failed to exert anti-inflammatory effects in the setting of PTPN2 knockdown. Thus, low levels of PTPN2 aggravated glucose-stimulated inflammation, while high levels of PTPN2 reduced it. Conclusion. PTPN2, an anti-inflammatory factor regulated by VDR, was reduced in T2DM CKD stages 1-2. Taken together, our results suggest that therapeutic strategies that enhance PTPN2 may be beneficial for controlling inflammation in T2DM.